Characterization of fracture properties of thin aluminuminclusions embedded in anisotropic laminate composites - Gabriella Bolzon; Vladimir Buljak; Emanuele Zappa (Fracture and Structural Integrity)
The fracture properties of thin aluminum inclusions embedded in anisotropic paperboardcomposites, of interest for food and beverage packaging industry, can be determined by performing tensile testson non-conventional heterogeneous specimens. The region of interest of the investigated material samples ismonitored all along the experiment by digital image correlation techniques, which allow to recover qualitativeand quantitative information about the metal deformation and about the evolution of the damaging processesleading to the detachment of the inclusion from the surrounding laminate composite. The interpretation of thelaboratory results is supported by the numerical simulation of the tests.